Is verbal reference impaired in autism spectrum disorder? A systematic review. (March 2018) - Malkin, Louise; Abbot-Smith, Kirsten; Williams, David
Background and aims: Pragmatic language is a key difficulty in autism spectrum disorder. One such pragmatic skill is verbal reference, which allows the current entity of shared interest between speakers to be identified and thus enables fluid conversation. The aim of this review was to determine the extent to which studies have found that verbal reference is impaired in autism spectrum disorder. We organise the review in terms of the methodology used and the modality (production versus comprehension) in which proficiency with verbal reference was assessed. Evidence for the potential cognitive underpinnings of these skills is also reviewed. Main contribution and methods: To our knowledge, this is the first systematic review of verbal reference in autism spectrum disorder. PsychINFO and Web of Science were systematically screened using the combination of search terms outlined in this paper. Twenty-four studies met our inclusion criteria. Twenty-two of these examined production, whereby the methodology ranged from elicited conversation through to elicited narrative, the 'director' task and other referential communication paradigms. Three studies examined reference interpretation. (One study investigated both production and appropriacy judgement). Four studies examined the relationship between appropriate usage of verbal reference and formal language (lexico-syntactic ability). Two studies investigated whether reference production related to Theory of Mind or Executive Functioning. Conclusion and implications: Across a range of elicited production tasks, the predominant finding was that children and adults with autism spectrum disorder demonstrate a deficit in the production of appropriate verbal reference in comparison not only to typically developing groups, but also to groups with Developmental Language Disorder or Down syndrome. In contrast, the studies of reference interpretation which compared performance to typical control groups all found no between-group differences in this regard. To understand this cross-modality discrepancy, we need studies with the same sample of individuals, whereby the task requirements for comprehension and production are as closely matched as possible. The field also requires the development of experimental manipulations which allow us to pinpoint precisely if and how each comprehension and/or production task requires mentalising and/or various components of executive functioning. Only through such detailed and controlled experimental work would it be possible to determine the precise location of impairments in verbal reference in autism spectrum disorder. A better understanding of this would contribute to the development of interventions.